Measurement of nuclear effects on ψ(2S) production in p-Pb collisions at √sNN=8.16 TeV - Acharya, Shreyasi; Angelov, Venelin; Arslandok, Mesut; Danisch, Meike; Feuillard, Victor; Glässel, Peter; Kim, Jiyoung; Kim, Minjung; Köhler, Markus Konrad; Leardini, Lucia; López, Jorge; Martin, Nicole Alice; et al. (Journal of high energy physics, 2020)
Inclusive ψ(2S) production is measured in p-Pb collisions at the centre-of-mass energy per nucleon-nucleon pair s NN $$ \sqrt{s_{NN}} $$ = 8.16 TeV, using the ALICE detector at the CERN LHC. The production of ψ(2S) is studied at forward (2.03 < ycms < 3.53) and backward (−4.46 < ycms < −2.96) centre-of-mass rapidity and for transverse momentum pT < 12 GeV/c via the decay to muon pairs. In this paper, we report the integrated as well as the ycms- and pT-differential inclusive production cross sections. Nuclear effects on ψ(2S) production are studied via the determination of the nuclear modification factor that shows a strong suppression at both forward and backward centre-of-mass rapidities. Comparisons with corresponding results for inclusive J/ψ show a similar suppression for the two states at forward rapidity (p-going direction), but a stronger suppression for ψ(2S) at backward rapidity (Pb-going direction). As a function of pT, no clear dependence of the nuclear modification factor is found. The relative size of nuclear effects on ψ(2S) production compared to J/ψ is also studied via the double ratio of production cross sections [σψ(2S)/σJ/ψ]pPb/[σψ(2S)/σJ/ψ]pp between p-Pb and pp collisions. The results are compared with theoretical models that include various effects related to the initial and final state of the collision system and also with previous measurements at s NN $$ \sqrt{s_{NN}} $$ = 5.02 TeV.
Im Titel steht der Ausdruck "sNN" unter dem Wurzelsymbol, "NN" ist dabei tiefgestellt
Mitglieder der ALICE-Collaboration: S. Acharya, V. Anguelov, M. Arslandok, M. C. Danisch, V.J.G. Feuillard, P. Glässel, J. Kim, M. K. Köhler, L. Leardini, J. A. Lopez, A. Marín, N.A. Martin, A. Ohlson, Y. Pachmayer, K. Reygers, R. Schicker, A. Schmah, M.O. Schmidt, B. Windelband, A. Yuncu [und weitere]
Gesehen am 16.11.2020